2012
DOI: 10.1103/physrevb.85.205136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strong disorder in a three-dimensional topological insulator: Phase diagram and maps of theZ2invariant

Abstract: We study the effect of strong disorder in a 3-dimensional topological insulators with time-reversal symmetry and broken inversion symmetry. Firstly, using level statistics analysis, we demonstrate the persistence of delocalized bulk states even at large disorder. The delocalized spectrum is seen to display the levitation and pair annihilation effect, indicating that the delocalized states continue to carry the Z2 invariant after the onset of disorder. Secondly, the Z2 invariant is computed via twisted boundary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 58 publications
1
36
1
Order By: Relevance
“…Support for this picture can be drawn from Ref. 52, in which careful numerical simulations on a disordered lattice model showed a finite-width region of metallic phase as the system was driven from the TI to the NI phase with increasing disorder strength while other parameters were held fixed. In our case the disorder strength remains approximately constant, but the ratio of disorder strength to energy gap varies with x, so that a metallic plateau may still be expected.…”
mentioning
confidence: 88%
“…Support for this picture can be drawn from Ref. 52, in which careful numerical simulations on a disordered lattice model showed a finite-width region of metallic phase as the system was driven from the TI to the NI phase with increasing disorder strength while other parameters were held fixed. In our case the disorder strength remains approximately constant, but the ratio of disorder strength to energy gap varies with x, so that a metallic plateau may still be expected.…”
mentioning
confidence: 88%
“…This characteristic has been indeed observed numerically for several symmetry classes. [11][12][13][14][15][16] However, a recent study 1 on the AIII symmetry class revealed that, in this particular case, the entire energy spectrum becomes localized as soon as the disorder is turned on, and it stays localized until an Anderson localization-delocalization transition builds up (from this entirely localized spectrum!) while crossing from one topological phase to another.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by several authors, 22,23,[28][29][30][31] disorder produces a phase transition between the topological insulator phase and a gapless metallic phase. This can be seen most directly using the self-consistent Green function, given by Eqs.…”
Section: Gapless Topological Phasementioning
confidence: 99%
“…[19][20][21][22][23] Studies of disorder led to additional surprises: It was shown that disorder can induce topological behavior in some trivial insulators, [24][25][26][27] and (more importantly for the current work) that disorder may close the gap in topological insulators, leading to a metallic phase. [28][29][30][31][32] In our work, we focus on the disorder-induced metallic phase in a simple test case of the Kane-Mele-Haldane honeycomb model. 1,33 Naively, once the disorder destroys the gap of a topological insulator, a simple metal emerges.…”
Section: Introductionmentioning
confidence: 99%